SOX13 as a potential prognostic biomarker linked to immune infiltration and ferroptosis inhibits the proliferation, migration, and metastasis of thyroid cancer cells - Ma, Yan-yan; Zhou, Wei-ye; Qian, Yue; Mu, Ying-ying; Zhang, Wei (Frontiers in Immunology, 2024)
BackgroundSOX13 is a transcription factor belonging to the SOX family. SOX proteins are critical regulators of multiple cancer progression, and some are known to control carcinogenesis. Nevertheless, the functional and clinical significance of SOX13 in human thyroid cancer (THCA) remain largely unelucidated.MethodsData on SOX13 expression were obtained through The Cancer Genome Atlas together with Gene Expression Omnibus. Co-expression, differential expression, and functional analyses of genes were investigated by databases. Associations between SOX13 levels, immune infiltration, ferroptosis, and immune checkpoint gene levels were analyzed. Genetic changes in SOX13 were investigated using CBioPortal. Associations between SOX13 levels and THCA clinicopathological features were analyzed and nomogram modeling for diagnostic and prognostic prediction. The influence of SOX13 on proliferation, migration, and metastasis was determined in KTC-1 and TPC-1 cell lines.ResultsSOX13 was significantly lower in THCA tumors compared to controls. In addition, upregulated SOX13 gene mutation were evident in thyroid cancer. SOX13-associated genes exhibited differential expression in pathways associated with thyroid cancer development. Significant associations were found between SOX13 levels, immune infiltration, ferroptosis, and immune checkpoint genes in THCA tissue. SOX13 levels correlated with THCA stage, histologic grade, and primary neoplasm focus types, and independently predicted overall and progression-free intervals. SOX13 expression effectively distinguished between tumor and normal thyroid tissue. Spearman correlations highlighted a significant relationship between SOX13 and ferroptosis-associated genes. Overexpression of SOX13 enhances the inhibition of RSL3 (iron death activator) on the cell viability of TPC-1. Higher SOX13 levels in Thyroid cancer cells may lead to reduced proliferation, migration, and metastasis by regulating ferroptosis.ConclusionReduced SOX13 expression inversely impacts patient prognosis. In addition, SOX13 strongly regulates cancer immunity and Ferroptosis. Hence, SOX13 has great promise as a bioindicator for both thyroid cancer prognosis and immune cell invasion.